Perbandingan kesegaran jasmani antara siswa yang tinggal di kota dan desa - Melati, Sesi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
This study aims to determine the comparison of the physical fitness level of students of SD Negeri 004 Ranah Sungkai, District XIII Koto Kampar with students of MI Negeri 03 Simpang Tiga Kota Pekanbaru. This research is a comparative study, which is comparing 2 groups, namely students of SD Negeri 004 Ranah Sungkai Kecamatan with students of MI Negeri 03 Simpang Tiga Kota Pekanbaru which focuses on grade V students. The subjects of this study were students of class V SD Negeri 004 Ranah. Sungkai totaling 20 male and female students with MI Negeri Simpang Tiga totaling 20 male and female students. Taking the value using an instrument in the form of 5 tests, namely, run fast 40 meters for boys and girls 30 meters, lift the body for 30 seconds, lie down for 30 seconds, jump upright and run long 600 meters. The data analysis technique used t test analysis. The results of this study obtained that most of the male students of SD N 004 Ranah Sungkai, XIII Koto Kampar District had a